Impact of salt accumulation in the bioreactor on the performance of Nanofiltration Membrane Bioreactor (NF-MBR) + Reverse Osmosis (RO) process for water reclamation - Tay, Ming Feng (2020)
The impacts of salt accumulation, through adjusting the solid retention time (SRT), in the bioreactor on the bioprocess as well as membrane performance of a high retention nanofiltration membrane bioreactor (NF-MBR) and subsequent reverse osmosis (RO) process for water reclamation are addressed in this study. The build-up of salts (i.e., Ca, Mg, PO4) is a function of SRT, hydraulic retention time (HRT) and membrane rejection. Despite the accumulation of salts, both NF-MBRs at SRT of 30 and 60 days, achieved (i) similar biodegradation efficiency; (ii) excellent organic removal (> 97%); and (iii) excellent ammonia removal (> 98%). Extending the SRT could improve the microbial bio-flocculation capability, but did not influence the microbial activity, viability, and community structure. However, more severe membrane fouling was observed in the NF-MBR with elevated salt levels, which was attributed to the greater formation of calcium phosphate scale and Ca-polysaccharides complex (i.e., irreversible fouling layer) as well as the cake-enhanced-osmotic-pressure (CEOP) effect. Although both NF-MBRs produced comparable quality of permeate, a higher RO membrane fouling rate was observed when the permeate of NF-MBR with SRT at 60 days was fed to the RO system, implying organic compositions in NF-MBR permeate may influence RO performance.